(ARTIKEL INI DICABUT-RETRACTED) Mesopotamia dan Mesir Kuno: Awal Peradaban Dunia (ARTIKEL INI DICABUT-RETRACTED) (Jurnal Adabiya, 2020)
The existence of civilization cannot be separated from the existence of human  beings. Mesopotamia  and Ancient  Egypt were the centers of the oldest civilization in the world. Both Mesopotamia and Ancient Egypt had typical characteristics. Mesopotamian  civilization was more non-physical compared to Egypt. Sciences were emphasized  more in Mesopotamia, while Egypt emphasized  religious aspects. Political systems in both areas were almost the same, that is, absolutism and considered the king as god. Mesopotamia  was more humanist  than Egypt. The effectiveness of both civilizations was determined much by political power and economy.THIS ARTICLE IS RETRACTED
Keywords: civilization; kingdom; ancient egypt; mesopotamia